(untitled) (TAMADDUN NURI JURNALI, 2024)
Thе аrticlе deals with the development of communicative competence is a fundamental component in the training of philological education students, as it equips them with the skills necessary for effective verbal and non-verbal communication across diverse contexts. This study explores modern approaches and methods to enhance communicative competence among students majoring in philology. Drawing on both theoretical frameworks and practical research, the paper identifies key strategies that foster linguistic, sociocultural, and pragmatic aspects of communication. These include task-based language teaching, interactive learning, and digital tools designed to simulate real-life communication scenarios.